Podróże edukacyjne synów szlacheckich w świetle korespondencji Jakuba Dunina z wojaży po Europie w latach 1699–1703 - Jarzębak-Kołodziejczyk, Joanna (Biuletyn Historii Wychowania, 2018)
The article aims to show the issue of educational travels of noble youth in the modern era. The source is the correspondence of Jakub Dunin from his journeys around Europe in 1699–1703, addressed to father Franciszek Świętosław. The mentioned letters (stored in the National Archives in Krakow in the Tomkowicz Archive from Kobiernice) provide important information referring to the reasons for travelling, travel expenses and the companions. Particularly noteworthy are colorful descriptions of the social life lived in European manors. For example, the author visited Versailles of Louis XIV and provided a detailed description of various ceremonies and court entertainment. Foreign journeys posed an opportunity to learn about foreign cultures, political systems or armies. This encouraged nobility sons’ reflections which they shared with relatives back in Poland. As a result, the travel correspondence abounds in individual interpretations, for example, of the then political developments on the international arena. When confronted with facts, they add extra value to the publication.